Cekap Enterprise: self control multi-cleaner / Tuan Hilman Nik Hilm [et al.] - Nik Hilmi, Tuan Hilman; Shamshuldin, Amir Hafsyam; Mohd Sari, Amira Nabihah; Mohd Sabandi, Ain Nazira; Ahmad Rasit, Nur Izatul Ashikin; Norazam, Nur Ezaitul Amirah (2016)
On our product, we have include the variety types surface of cleaner such as fabric and brush for the variety type of surface floor such as tiles, hard tiles and many else.